Implementation of Family Hope Program Policy in Lhokseumawe City - Fauzan Fauzan; Dahlan Arahman; Nirzalin Nirzalin (Malikussaleh Social and Political Reviews, 2021)
The purpose of this study is to find out the Implementation of Lhokseumawe City Government Policy on Family Hope Program (PKH), to know the constraints and the efforts made by the government in effectively supporting the Family Hope Program, and to know the process of collecting data of the very poor households (RTSM) as the target as PKH. The theory used in this research is the George Edward III Policy Implementation which consists of four variables namely Communication, Resources, Disposition and Bureaucratic Structure. The method used in this study is a qualitative method with a descriptive type. Data collection is done through observation, interviews and documentation. The results of this study show that: First, the Implementation of the Family Hope Program Policy in Lhokseumawe City is still not effective, the information about the hope family program (PKH) has not been fully understood by the society. Second, the constraints of the implementation of the policy interms of facilities to supporting operations are still lacking, the (PKH) benficiaries are not committed to the health and education of their children, the supervision and evaluation of the program has not run as expected. Third, efforts to providing special guidance through chaperones so that the families of PKH recipients have a commitment to health checks and the course of education. Fourth, the system of data collection of recipients of the hope family program (PKH) has not been carried out as the mechanism of implementation of the Family Hope Program (PKH) is proven not all gampong in Lhokseumawe City conduct village deliberations (Musdes) in determining very poor households (RTSM). Implementation of the hope family program (PKH) policy in Lhokseumawe City in terms of communication has not been done effectively because the program information provided to the family of the recipient of the hope family program (PKH) has not had a positive influence on the recipient's family life.